2022
DOI: 10.1371/journal.pone.0268241
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and epidemiological characteristics of COVID-19 after one year of pandemic in Jakarta and neighbouring areas, Indonesia: A single center study

Abstract: We determined the prevalence and epidemiological characteristics of COVID-19 in Jakarta and neighboring areas, Indonesia from March 2020 to February 2021, based on nasopharyngeal/oropharyngeal (NP/OP) swab specimens that were tested at the Eijkman Institute for Molecular Biology, Jakarta. NP/OP swab specimens were collected from COVID-19 suspects or individuals in contact tracing programs from primary healthcare centers (PHC) and hospitals. The specimens were screened for the SARS-CoV-2 by qRT-PCR. Demography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
3
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 17 publications
0
13
3
6
Order By: Relevance
“…Nevertheless, in the first wave of the pandemic, the mortality rate in this population was lower than that in other studies from a different tertiary hospital in Mexico [ 27 ]. In addition, other studies from Brazil and Indonesia have reported higher mortality rates, with 15% and 40%, respectively [ 28 , 29 ]. This difference might be due to the significantly higher number of patients in this study, which includes hospitalized and ambulatory patients from the four waves of the pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, in the first wave of the pandemic, the mortality rate in this population was lower than that in other studies from a different tertiary hospital in Mexico [ 27 ]. In addition, other studies from Brazil and Indonesia have reported higher mortality rates, with 15% and 40%, respectively [ 28 , 29 ]. This difference might be due to the significantly higher number of patients in this study, which includes hospitalized and ambulatory patients from the four waves of the pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…Viral RNA was extracted from plasma samples and used as a template for quantitative RT-PCR targeting a 200 bp region of the envelope (E1) gene [ 47 ]. Recently, the real-time RT-PCR technique was employed to detect and quantify SARS-CoV-2 in specimens collected from COVID-19 suspects or persons in contact tracing programs [ 48 , 63 , 64 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Nasopharyngeal/oropharyngeal swabs have typically been used to confirm the clinical diagnosis. Notably, SARS-CoV-2 could also be detected in specimens from other sites such as bronchoalveolar lavage fluid, sputum, fiber bronchoscope brush biopsy, feces, and blood [ 64 , 70 ]. The real-time PCR method was applied to detect SARS-CoV-2 in more than 64,000 specimens collected from COVID-19 suspects or individuals in contact tracing programs in Jakarta and neighboring areas, Indonesia, within the first year of the COVID-19 pandemic [ 64 ].…”
Section: Detection and Quantification Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…SARSCoV-2 can infect people of all ages. However, epidemiological studies indicate that older men (Setiadi et al, 2022), smokers, and patients with comorbid conditions such as diabetes mellitus, chronic obstructive lung disease, heart disease, and others have higher incidence and severity of the condition (Fu et al, 2020;Xiaofan Liu et al, 2020). Symptomatic or light instances make up 55% of cases in children and adolescent, moderate cases make up 40%, severe cases make up 5%, and very serious cases make up just 1% (CDC, 2020).…”
Section: Introductionmentioning
confidence: 99%